2009
DOI: 10.1074/mcp.m900107-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Processing and Presentation of T-cell Epitopes from Chlamydia trachomatis with Relevance in HLA-B27-associated Reactive Arthritis

Abstract: Chlamydia trachomatis triggers reactive arthritis, a spondyloarthropathy linked to the human major histocompatibility complex molecule HLA-B27, through an unknown mechanism that might involve molecular mimicry between chlamydial and self-derived HLA-B27 ligands. Chlamydia-specific CD8؉ T-cells are found in reactive arthritis patients, but the immunogenic epitopes are unknown. A previous screening of the chlamydial genome for putative HLA-B27 ligands predicted multiple peptides that were recognized in vitro by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…ReA is strongly correlated with the expression of a particular MHC class I allele, HLA-B27 (47)(48)(49). Animal models have shown that chlamydia-reactive CD8 ϩ T cells can recognize self-peptides bound to HLA-B27 (50-52).…”
Section: Discussionmentioning
confidence: 99%
“…ReA is strongly correlated with the expression of a particular MHC class I allele, HLA-B27 (47)(48)(49). Animal models have shown that chlamydia-reactive CD8 ϩ T cells can recognize self-peptides bound to HLA-B27 (50-52).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the recent reports that certain cytokine profiles of anti-chlamydial immune effectors, are critical for preventing immunopathology [10,11] may offer appropriate screening methods for antigen immuno-toxicity or potential for inducing protective immunity; accordingly, the induction of an appropriate immune profile that include IFN-γ or an inappropriate cytokine profile, such as the absence of IFN-γ or a predominantly Th2 or T17 response [10][11][12][13], and presence of potentially pathogenic properties in the antigen [14][15][16][17][18] are promising vaccine antigen screening and discovery approaches. In addition, the profile of cytokines and immune effectors of an anti-chlamydial immune response in infections with and without pathologic complications may also provide a useful molecular and immunological biomarker for predicting chlamydial pathologies.…”
Section: Trachomatis Genital Infection Is the Most Common Bacterialmentioning
confidence: 99%
“…Posteriormente, se expresó un fragmento proteico que incluía parte de la secuencia homóloga a B27 de esta ADN-primasa bacteriana en líneas celulares B27-positivas, probando que la construcción proteica era procesada y presentada "in vivo" por B*27:05 16 . Además, mediante inmunoproteómica comparada, se demostró que un péptido bacteriano homólogo al ligando propio de B*27 era procesado y presentado endógena-mente, demostrando la existencia de mimetismo molecular 17 . Sin embargo, a pesar de todas estas evidencias, aún no se ha podido constatar la existencia de péptidos artritogénicos.…”
Section: Hla-b27unclassified